CROalertNet – System architecture - Filipović, Antun Matija; Bralić, Tina; Bralić, Vladimir (Crisis Management Days, 2025)
This paper expands on the previously presented idea for a new information system – CROalertNet. CROalertNet is a multi-platform, multi-module information system designed to use mobile devices to assist civilians during crisis events and which is capable of maintaining a basic degree of functionality in offline mode, which is the expected state during a major crisis event. Our previous work described the need for such an information system and presented, in detail, the idea of a single module – a bomb shelter location mobile application. The previously presented module is a small part of the whole system and in this paper, we expand on the system by proposing the architecture of the CROalertNet information system. A fully developed CROalertNet system would greatly enhance communication capabilities during crises and enable civilians access to vital information even when communication channels (such as mobile networks) break down or function in a reduced capacity due to network congestion.